A scaled test on the damage and vibration behavior of reinforced concrete nuclear containment subjected to a large aircraft impact. (1st October 2022) - Wang, F.; Liu, J.B.; Bao, X.; Sun, Y.L.; Lu, X.H.; Wang, D.
Highlights: A 1/15 scaled impact test was performed to assess the damage and vibration behavior of the RC nuclear containment under an aircraft impact. An impact damage upper limit reference value for the nuclear containment under a large aircraft impact was obtained. The results can be used for validation of finite element simulation computational methods and models. Abstract: After the 9/11 terrorist attacks in the United States, the ability of nuclear power plants (NPPs) to resist the malicious impact of large commercial aircraft has become a focus in the nuclear security field. To investigate the damage and vibration characteristics of NPP containment against a large aircraft impact, an experiment of an airplane impacting a reinforced concrete (RC) nuclear containment structure model was carried out using a rocket sled launching facility. In the experiment, a 1/15 scaled RC nuclear containment structure model was designed and built according to a certain type of NPP building prototype. The total impact process was recorded by a high-speed photography system. Moreover, the corresponding test data and physical parameters of the nuclear containment model were obtained, including the damaged area of the RC nuclear containment model, acceleration time histories, reinforcement steel strain time histories, etc. It is found that the containment model exhibits local damage when the large aircraft model collides with a velocity of 142.3 m/s. However, reinforcement prevents the large aircraft model from perforating the NPP containment effectively. In this paper, the damage and failure rules and characteristics of RC nuclear containment under the impact of a large aircraft are discussed, and the impact vibration response characteristics of nuclear containment are preliminarily analyzed based on the test. The related studies and conclusions can provide a basis for NPP structural optimization and the safety assessment of large commercial aircraft collision problems and can also provide data support for finite element (FE) modelling.